Networked Control Systems - Bemporad, Alberto; Heemels, Maurice; Johansson, Mikael; SpringerLink (Online service) (London : Springer London, 2010)
There has been a recent surge in research activities related to networked control of large-scale systems. These "cyber-physical" systems can be found throughout society, from industrial production plants, to water and energy distribution networks and transportation systems. They are characterized by tight coordination of a pervasive sensing infrastructure, distributed computing elements, and the physical world. Developed from work presented at the 3rd WIDE PhD School on Networked Control Systems held in Siena in July 2009, Networked Control Systems contains tutorial introductions to key research topics in the area of networked control. Classroom pdf slides used in the PhD school presentations can be downloaded to assist academic teachers in using the material with their own classes. The contributing authors are renowned experts in the field so that the book provides a single point of entry to a diverse and exiting research area. PhD students and researchers in control and industrial communications, as well as practitioners in the area of large-scale control systems will find the contents of this volume highly informative.
The Importance, Design and Implementation of a Middleware for Networked Control Systems -- Wireless Networking for Control: Technologies and Models -- A Survey on Distributed Estimation and Control Applications Using Linear Consensus Algorithms -- Distributed Optimization and Games: A Tutorial Overview -- Decentralized Model Predictive Control -- Decentralized Control -- Stability and Stabilization of Networked Control Systems -- Feedback Control over Limited Capacity Channels -- Event-Triggered Feedback in Control, Estimation, and Optimization.
Keywords: Computer science; Computer network architectures; Systems theory; Telecommunication; Computer Science; Computer Systems Organization and Communication Networks; Systems Theory, Control; Control; Communications Engineering, Networks